The High-Spin Heme bL Mutant Exposes Dominant Reaction Leading to the Formation of the Semiquinone Spin-Coupled to the [2Fe-2S]+ Cluster at the Qo Site of Rhodobacter capsulatus Cytochrome bc1 - Sarewicz, Marcin; Pintscher, Sebastian; Bujnowicz, Łukasz; Wolska, Małgorzata; Artur Osyczka, (Frontiers in Chemistry, 2021)
Cytochrome bc1 (mitochondrial complex III) catalyzes electron transfer from quinols to cytochrome c and couples this reaction with proton translocation across lipid membrane; thus, it contributes to the generation of protonmotive force used for the synthesis of ATP. The energetic efficiency of the enzyme relies on a bifurcation reaction taking place at the Qo site which upon oxidation of ubiquinol directs one electron to the Rieske 2Fe2S cluster and the other to heme bL. The molecular mechanism of this reaction remains unclear. A semiquinone spin-coupled to the reduced 2Fe2S cluster (SQo-2Fe2S) was identified as a state associated with the operation of the Qo site. To get insights into the mechanism of the formation of this state, we first constructed a mutant in which one of the histidine ligands of the iron ion of heme bLRhodobacter capsulatus cytochrome bc1 was replaced by asparagine (H198N). This converted the low-spin, low-potential heme into the high-spin, high-potential species which is unable to support enzymatic turnover. We performed a comparative analysis of redox titrations of antimycin-supplemented bacterial photosynthetic membranes containing native enzyme and the mutant. The titrations revealed that H198N failed to generate detectable amounts of SQo-2Fe2S under neither equilibrium (in dark) nor nonequilibrium (in light), whereas the native enzyme generated clearly detectable SQo-2Fe2S in light. This provided further support for the mechanism in which the back electron transfer from heme bL to a ubiquinone bound at the Qo site is mainly responsible for the formation of semiquinone trapped in the SQo-2Fe2S state in R. capusulatus cytochrome bc1.